Peran Mikroorganisme Tanah dalam Meningkatkan Kesehatan Tanah dan Hasil Pertanian Organik - Krisna Sari Dohare; Mesrana Putri Lahagu; Putri Novi Kristiani Waruwu (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Soil microorganisms have an important role in improving soil health and supporting sustainable organic agriculture. They contribute to the decomposition of organic matter, management of nutrient cycles, control of pathogens, and improvement of soil structure. This research explores the role of microorganisms, such as bacteria, mycorrhizal fungi, and actinobacteria, in supporting soil fertility by increasing the availability of nitrogen, phosphorus, and potassium for plants, as well as improving soil quality by increasing water retention capacity and reducing erosion. These microorganisms also act as biocontrol agents that inhibit pathogens, thereby reducing the need for chemical pesticides. However, managing soil microorganisms faces major challenges due to environmentally unfriendly agricultural practices, such as the use of pesticides and chemical fertilizers. This research emphasizes the importance of implementing sustainable agricultural principles to conserve soil microorganisms and maintain the health of the soil ecosystem as a whole. This study aims to provide insight into the role of soil microorganisms in increasing organic agricultural yields and recommend more effective and environmentally friendly management. These findings are expected to support the development of more productive and sustainable organic agriculture.